An exploration of labour broking in the auditing industry in Gauteng, South Africa - Kgwete, Podile (An exploration of labour broking in the auditing industry in Gauteng, South Africa, 2023)
Labour broking is a controversial topic in South Africa and, invariably, what comes to mind is employees being exploited. The typical employees under this arrangement are people with no tertiary training, the so-called blue-collar workers. This is perhaps the reason why there are limited studies conducted on labour broking in high-end professions like auditing. Recently there has been a huge advent of labour broking in the auditing profession led by two labour brokers, Makosi and Sapro. They have found a niche market where they outsource South African Auditors to American and European Audit firms on a contract basis. This has been disruptive to the South African market as it has increased the demand for accountants. This has meant that audit firms and corporate South Africa have had to compete for accountants in the international market more than ever. We have studied here the phenomenon in the hope of understanding why these professionals choose to work under these circumstances. The key findings were that there is a myriad of factors why auditors in South Africa continue to choose this way of working. Great remuneration has come up often, while experience and exposure to working with international clients were also listed as attractive benefits. Above all, most participants spoke about the great work culture, as opposed to what some have experienced when working for the average audit firm in South Africa. This has ground-breaking applications in the labour broking industry and shows that this model can be applied safely and fairly to contracted employees. Moreover, labour broking provides flexibility in the labour market, which is beneficial to both job seekers and employer
A research proposal submitted in partial fulfillment of the requirements for the degree of Master of Business Administration. to the Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Labour Broking; Auditing; Chartered Accountant; Temporary employment services; UCTD; SDG-8: Decent work and economic growth